Neuroethics - Gouta, Chrysoula (Bioethica, 2023)
This review was written in the framework of the Bioethics Course of the MSc Toxicology and is an attempt to briefly revise the history of the inconspicuous branch of Neuroethics, which, despite making a deafening appearance two decades ago, it gradually lost the interest of the scientific community. The reasons for the devaluation of a promising field like this are searched and thoroughly analyzed throughout the review, while this decline is attributed to the lack of semantic completeness and systematic methodology of the novice field and to the overall deceleration in the development of neurosciences. In addition, the article attempts to clearly define the terms and concepts that play a crucial role in the understanding of the field in question and cites a primitive classification system that includes Empirical Neuroethics, Theoretical Neuroethics and Methodological Neuroethics, with the latter being more of a wishful thinking rather than an applied scientific sub-discipline. Finally, some key contemporary issues in Neuroethics, such as informed consent, neurogenetics and the brain-spirit relationship, are discussed and commented on with reference to the principles of Philosophy and Theology.